The EU-Georgia trade agreement: The impact on agricultural trade and welfare - Ulrich Koester (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
The EU has signed new agreements with Ukraine, Moldavia, and Ukraine, the so-called Deep and Comprehensive Free Trade Agreement (DCFTA). This policy brief only focuses on Georgia to exemplify the mythology and some important specifics of the participating countries that differ somewhat, but are important for assessing the impact. The agreement with Georgia became effective in September 2016; therefore, accurate estimation of the quantified effects was delayed for some time. This policy brief focusses on the free trade agreement on agricultural products. Georgia benefits from trade preferences for import to the EU and the EU likewise from exports to Georgia. It is foreseen that tariffs will be abolished completely in the future, but at present it is only Georgia which has abolished tariffs for imports from the EU. The EU has only reduced the World Trade Organization (WTO) bounded rates and, in addition, it still applies the socalled entry price system and even quotas for imports of garlic. Effects on trade might be important because the EU still highly protects agricultural imports and thus the standard of living for the 50 percent of Georgians living mainly from farming may improve. The findings are that Georgia may gain in total, if traders live in Georgia. The gain results from both redirection of Georgian exports from other destinations and additional exports of Georgian products. These additional exports to the EU may be replaced by additional imports from low price suppliers on the world market.
urn:nbn:de:gbv:3:2-76055
Keywords: 330